ANALISIS UPAYA PENANGGULANGAN KEBAKARAN DI GEDUNG BOUGENVILLE RUMAH SAKIT TELOGOREJO SEMARANG - Minati Karimah; Bina Kurniawan; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2016)
Fires often occur to unintended consequences such as material losses, work processes, environmental damage or a safety threat to human lives. Bougenville Room Telogorejo Hospital Semarang is do not have a specific functions team to fire prevention. This study aimed to analyze the fire-fighting effort in the building of the hospital. This research was a descriptive qualitative research observation and in-depth interviews. The subjects of this research were 6 people as key informants and 2 as triangulation informant. The results showed that Telogorejo hosiptals has fire fighting abilities system. The availability of fire fighting unit based on labour ministry decree no. 186 / MEN / 1999 were 52.17%, then the compliance of standard operating procedures for fire based on Ministry of Public Workers Decree No.11 / KPTS / 2000 were 100%. Active fire protection systems include: the level of compliance in fire extinguishers based on labour ministry law no. 4 / MEN / 1980 were 66.67%, hydrants based on SNI 03-1745-2000 were 50%, sprinkler based on 03- 3989-2000 were 0%, and the fire alarm based on labour ministry law no. 2 / MEN / 1983 were 50%. Emergency facilities include: level of compliance in emergency staircases based on SNI 03-1746-2000 were 72.7%, and exit signages based on SNI 03-6574-2001 were 69.23%. It can be concluded that fire fighting abilities in Bougenville Room Telogorejo hospitals has the compliance level of fire-fighting were varying. Therefore, the hospital needs to complete such as fire-fighting team, fire extinguisher, hydrants, sprinklers, fire alarm, emergency stairs, and exit signages